THERMOELECTRIC DEVICES TO PROVIDE THERMAL BLOCK MODE ELECTRONIC SYSTEMS - T. A. Ismailov; A. T. Rashidhanov; Sh. A. Yusufov (Вестник Дагестанского государственного технического университета: Технические науки)
The article deals with thermoelectric cooling (TEC) device to provide thermal mode power electronics systems cluster design, are areas of constructive solutions use the feasibility study of the device, a description of the experimental facility and methodology of the experiment, the dependences of temperature on the simulator of the electronic board from the exhaust of the feasibility study power, temperatures of hot and cold junctions, the speed of the air flow and the distance between the electronic boards.